Variety of German Chamomile (Matricariarecutita l.) Secondary Compounds in Different Planting Dates in Iran - Mohammadreza Naderidarbaghshahi (Journal of Global Pharma Technology, 2017)
This study was conducted in the Research – Educational field of Isfahan Islamic Azad University (Khorasgan) Branch, Faculty of Agriculture, in the crop year 2014-2015, in order to evaluate the quantitative and qualitative aspects of German chamomile in different planting dates of chamomile. In this study, quantitative and qualitative characteristics of German chamomile were studied during three planting dates in mid-October, mid-November and mid-March in a Randomized Complete Block Design. In this study, the planting date of chamomile leads to relatively large changes in the chemical composition and chamomile yield and the amounts of Chamazulene and its Bisabolol oxide A, so that, along with delay in chamomile planting date, dry flower yield performance decreased, but Chamazulene and Bisabolol oxide A of that chamomile has increased. In line with the comparison between these three planting dates, in terms of the performance of produced chamomile, mid-October German chamomile planting with 1602 kg per hectare of chamomile dry flower had the most amount of dry flower yield and early-March planting with 1/9 kilograms per hectare of essential oil production and 0/14 kilograms per hectare Chamazulene had the highest amount of essential oil yield and Chamazulene and it can be recommended for the study region